Evaluating ecosystem multifunctionality in tree-based intercropping: a case study from southern Québec, Canada - Rivest, David; Martin-Guay, Marc-Olivier; Hébert, Ève-Marie; Dulac, Samuel; Cogliastro, Alain; Maheu, Audrey (Frontiers in Agronomy, 2025)
Agroforestry is increasingly recognized as an effective tool for enhancing multifunctionality in agroecosystems globally, improving land-use efficiency and delivering multiple ecosystem services (ES). This study investigates the multifunctionality of tree-based intercropping (TBI) systems, which integrate widely spaced rows of trees with agricultural crops and can be adapted to different climates. We assessed spatial gradients of 11 ES indicators based on field measurements taken at increasing distances from the tree rows within a temperate TBI system of 50 trees ha-1, aged 7 to 10 years. These indicators were compared between the TBI system and agricultural control plots, which were managed similarly to the cultivated alleys in the TBI system but without trees. We measured light availability, soil moisture and crop yields (forage and wheat) across cultivated alleys associated with three tree species compositions: 1) red oak in monoculture, 2) hybrid poplar in monoculture, and 3) a mix of red oak and hybrid poplar alternating along the row. The greatest variation in ES indicators within the cultivated alleys, compared to the agricultural controls, was frequently observed nearest to the tree rows. Specifically, yields of annual crops (wheat and corn), soil moisture, P supply, NO3- leaching rates and bulk density decreased, while potential evaporation increased in areas closest to the tree rows, in contrast to measurements taken near the alley centre and in the control plots. Other ES indicators, including forage yield, N and K supplies, and soil C stocks, remained unaffected by the TBI system. Our results suggest that trade-offs between ES may occur at fine scales and be location-specific within TBI systems. Plots containing poplar (alone or mixed with red oak) exhibited lower soil moisture and light availability compared to those with red oak only, resulting in a greater decrease in wheat yield at the tree-crop interface. Conversely, C stocks in fast-growing poplar biomass were substantially higher than those in red oak. We conclude that composition of tree species is crucial in determining trade-offs in ES delivery within TBI systems. At the system level, we found comparable levels of multifunctionality between TBI and control plots, likely due to the limited sample size of aggregated data.